2013
DOI: 10.1111/cas.12167
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of CD163+ tumor‐associated macrophages in patients with adult T‐cell leukemia/lymphoma

Abstract: In several malignant tumors including lymphoma, macrophages that infiltrate tumor tissues are called tumor-associated macrophages (TAMs). We discovered that TAMs, especially the CD163 + alternatively activated phenotype (M2), were closely involved with progression of adult T-cell leukemia ⁄ lymphoma (ATLL). We used CD68 (a pan-macrophage marker) and CD163 (an M2 marker) to immunostain 58 ATLL samples. Statistical analyses showed that a high number of CD68 + TAMs and an increased percentage of CD163 + cells amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 39 publications
3
106
2
1
Order By: Relevance
“…These findings suggest that Sirpα + DCs are most capable of supporting T-ALL growth, although our data demonstrate that other myeloid cells likely contribute. Similarly, monocytes differentiated into M2 macrophages were shown to directly promote proliferation of adult T-cell leukemia/lymphoma cell lines (52). Thus, it will be important to evaluate the respective roles of tumor-associated Sirpα + and Sirpα − DCs, as well as other myeloid subsets in supporting T-ALL growth.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that Sirpα + DCs are most capable of supporting T-ALL growth, although our data demonstrate that other myeloid cells likely contribute. Similarly, monocytes differentiated into M2 macrophages were shown to directly promote proliferation of adult T-cell leukemia/lymphoma cell lines (52). Thus, it will be important to evaluate the respective roles of tumor-associated Sirpα + and Sirpα − DCs, as well as other myeloid subsets in supporting T-ALL growth.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the number of CD68-positive macrophages in ATLL tissues did not correlate with overall survival (P = 0.25), whereas patients with a large number of CD163-positive macrophages (C250 cells/mm 2 tumor area; n = 37) had worse outcomes than those with a small number (\250 cells/mm 2 tumor area; n = 36) (P = 0.05). Moreover, a higher ratio of CD163-positive to CD68-positive macrophages in ATLL significantly correlated with worse overall survival (P = 0.039), while multivariate analysis demonstrated that the number of CD163-positive macrophages constitutes an independent prognostic factor [24].…”
Section: Ccl18/cx3cr1 and Atllmentioning
confidence: 98%
“…The experimental procedure was approved by the Kumamoto University Review Board (Kumamoto, Japan). We previously published characteristics of this same set of ATLL specimens, and thus, the numbers of CD68-and CD163-positive cells published in that previous report (11) were used in this study.…”
Section: Tim-3-expressing Atll Cell Linesmentioning
confidence: 99%
“…We previously demonstrated that macrophages induced ATLL cell proliferation and that a higher density of tumor-associated macrophages (TAMs) in ATLL tissues was closely associated with a poor clinical prognosis (11). It was also found that direct contact with macrophages induced ATLL cell activation, although the detailed mechanisms have not yet been elucidated (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation